Brazil : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. (IMF Staff Country Reports; Country Report ;, 2021)
Economic performance has been much better than expected, in part due to the authorities' forceful policy response. Nevertheless, Brazil's long-standing challenges of low growth, high debt, and elevated levels of poverty and inequality have been exacerbated by the pandemic. Tragically, more than 550,000 Brazilians have died from COVID-19.